Study on gender equality: overview the reality of muslim feminist movement - Zainol, Nur Zainatul Nadra Binti (Serials Publications, 2017)
Nowadays, the Muslim communities are confronted with the grups of people thatdemand for the opening of the gate of ijtihad by putting the rational first before the Quran and al-Sunnah. These groups do not disclose themselves as people who reject religion, but they hide behind the idea of reviewing the religion. They reassess the Shari’a and fiqh statutes and reject any interpretation of scholars on religious grounds. For them, the laws in Islam must be compatible with the current realities, even they have to deny the laws that have been thabit with Islamic texts for qatc i. Among the thinkers are the feministswho struggle for women’s rights. They argue that there are some laws in the Quran which have oppressed and discriminated women. Thus, these Muslim feminists who fight to defend the Muslim women,standing up for the issue of gender equality in the hope to revise the Shari’a laws in accordance to theirliking. This article aims to analyse the issues of gender equality brought by feminist groups to explain the reality in Malaysia. The results showed that the issues propagated by them is theconsequenceof the Quran re-interpretation. The implications of this study indicate that the movement should be observedand taken seriously because the idea of gender equality is not initially derived from Islam. Thus, the thoughts of having the openness in ijtihad by putting rational over al-Quran and al-Sunnah like what the feminists advocate must be controlled from penetrating into the minds of the Muslim community.